PERBEDAAN KEJADIAN INFEKSI CACING ANTARA PETUGAS PENGANGKUT SAMPAH YANG MENGGUNAAN ALAT PELINDUNG DIRI DENGAN PETUGAS PENGANGKUT SAMPAH YANG TIDAK MENGGUNAKAN ALAT PELINDUNG DIRI - Lezdyana Nur Islami; Sulastrianah Sulastrianah; Wa Ode Sitti Asfiah Udu (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Soil  Transmitted  Helminth  (STH)  infection  globally  spread  around  the  worlds.  Incidence  of  helminth infection  more  common  in  childrens,  but  adult  with  special  job  like  garbage  workers  have  same  risk  with  that childrens. The aim of this study is to determine differences between usage of personal protective equipment with the helminth  infection  among garbage  workers that  completely  used  personal  protective  equipement  and  that  not completely used . The method of this study is an observational with cross sectional design. Population in this study are garbage workers at Sanitary Service Wakatobi Regency. Sampling method using total sampling with 59 samples. The data about usage of personal protective equipement have done by observation and faecal examination by direct slide. The differences analysed statistically using Chi-Square test. As a result, it is obtained that among the workers that  not completely using  personal  protective  equipment,  there  27  (60%) samples  are infected  and 18  (40%) samples  are  not  infected.  Among  the  workers  that completely using  personal  protective  equipment, there  is  4 (28,6%) samples are infected and 10 (71,4%) samples are not infected (p = 0,04). The conclusion of this study is there was relation between usage of personal protective equipment with helminth infection in garbage workers. Key Words: Helminth infection, garbage workers, personal protective equipment